2018
DOI: 10.1155/2018/5874184
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness of New Material Diapers versus Standard Diapers for the Prevention of Diaper Rash in Chinese Babies: A Double-Blinded, Randomized, Controlled, Cross-Over Study

Abstract: Background Diaper rash, also known as diaper dermatitis (DD), is a very common skin condition in infants, and use of disposable diapers with breathable materials is an effective approach for the management of diaper rash. In China, new material diapers and standard diapers are currently the two most commonly used disposable diapers. This study aimed to compare the effectiveness of new material diapers versus standard diaper for the prevention of diaper rash in Chinese babies. Methods A total of 80 eligible bab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…The new material diaper used in the study conducted by Yuan C et al also had similar features. Therefore, High Air-Through Soft Diaper in the present study also showed similar superiority over the standard diaper in babies as that observed in the study conducted by Yuan C et al 4 There are some limitations to the present study. Climate factors are confounding factors in such types of studies as they have effects on skin irritation and skin barrier functions.…”
Section: High Air-through Soft Diaper Vs Standard Diapersupporting
confidence: 83%
See 3 more Smart Citations
“…The new material diaper used in the study conducted by Yuan C et al also had similar features. Therefore, High Air-Through Soft Diaper in the present study also showed similar superiority over the standard diaper in babies as that observed in the study conducted by Yuan C et al 4 There are some limitations to the present study. Climate factors are confounding factors in such types of studies as they have effects on skin irritation and skin barrier functions.…”
Section: High Air-through Soft Diaper Vs Standard Diapersupporting
confidence: 83%
“…Thus, the current study appears to be more conclusive. 4 In the present study we found that, after 2 weeks, the mean total diaper rash score was increased significantly from the baseline in both Group A (High Air-Through Soft Diaper-Standard diaper) and Group B (Standard diaper-High Air-Through Soft Diaper). We mention at the end, these first 2 weeks results were also affected by increasing environmental temperature.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Novel diapers having improved design and materials outperform standard diapers in better permeability and odour control via chitosan addition to the fibres mix, better absorption via bamboo fibre blends and antimicrobial function via sustainable herbal finishes [11][12][13][14]. Traditional diapers, bio-degradable diapers and reusable cloth diapers were compared to each other in a few studies and findings revealed that bio-degradable diapers are the most ecofriendly ones followed by reusable cloth diapers while the first two provided better performance due to reuse and cleaning deteriorates many properties of reusable cloth diapers in extended usage [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%